Present Status of Fish Diversity of the Kaptai Lake, Bangladesh - Arafeen, Mohammad Shamsil; Siam, M A Habib; Tasnim, Jarin; Owaresat, J K; Asek, Abdullah Al; Newaj, AHM Shihar; Kibria, Md Manzoorul; Haidar, Md Istiaque (Journal of the Bangladesh Agricultural University, 2024)
Kaptai Lake (KL) is the biggest manmade lake in Bangladesh and plays a significant role for local fisheries by creating an excellent environment for various indigenous species. This study pursues to enhance the understanding on fish diversity in Kaptai Lake by attempting to explore the present status of fish populations within the reservoir taking into specific focus on evaluation of conservation management priorities and additional conservation needs. The study was conducted during January–December 2023 at five different sites of the Rangamati district, namely Banarupa Bazar, BFDC Ghat (Rangamati), BFDC Ghat (Kaptai), Reserve Bazar and Tabalchari Bazar. We identified 80 fish species representing the 11 orders and 28 families where Cypriniformes had the highest percentage (38.75%), and ranged from 1.25% to 22.50% for the other orders. The diversity indices, Shannon-Wiener (Hʹ), Pielou’s evenness index (Jʹ) and species richness (SR) were found to be low and uneven in KL based on different seasons. The maximum fish catch was recorded in September (1,855.55 metric tons), and the minimum fish catch ever caught by April (112.24 metric tons). The diversity of Kaptai Lake fish stock is alarmingly threatened due to sustainable human and natural adversities. These results contribute valuable data for conservation purposes and management of Kaptai Lake for biodiversity protection in the years to come. J Bangladesh Agril Univ 22(4): 506–516, 2024